Providing engineers with OARS and EARS: Effects of a skills-based vocational training in Motivational Interviewing for engineers in higher education - Klonek, Florian; Kauffeld, S. (2015)
Purpose-Motivational Interviewing (MI) is a vocational communication skill from the helping professions. Verbal skills in MI are summarized under the acronyms OARS and EARS (open-ended questions/elaborating, affirmations, reflections, and summaries). The purpose of this paper is to outline how MI provides important skills for engineers, and demonstrate skill assessment by using an observation-based scientific approach. Design/methodology/approach-Totally, 25 engineering students took part in a skill-based MI training. Quality assurance of the training was assessed by using a repeated measurement design with multiple measures: systematic observations from recorded interactions and self-reported and standardized performance measures. Two external observers reliably coded the recorded conversations using the MI skill code. Findings-Trainees showed a significant increase of verbal skills in MI. Directive-confrontational behaviors decreased after training. Self-reported and performance measures indicated significant increases in MI post training. Conversational partners in the post-training condition showed significantly more motivation in comparison to partners before the training. Research limitations/implications-The main limitation of the study is the small sample size. However, training effect sizes showed large effects on verbal skills. Practical implications-Communication skills in MI can be taught effectively for a technical population. This study suggests that MI is effective within the higher education of technical professions who have to deal with motivational issues. Observational measures can be used for quality assurance purposes, but also serve as a feedback instrument for work-based learning purposes. Originality/value-This is the first study to evaluate training in MI for engineers using a multi-method approach with observational measures.